The Impact of Federal Crop Insurance on the Conservation Reserve Program. (August 2019) - DeLay, Nathan
Abstract : I directly estimate the acre-for-acre impact of crop insurance participation on Conservation Reserve Program (CRP) enrollment at the county level. The government may be sponsoring competing interests if subsidized insurance expands production at the expense of CRP. I employ an instrumental variables technique to correct for endogeneity in insurance decisions. Results suggest that an additional 1, 000 acres insured reduces CRP enrollment by about three acres, though effect sizes vary by region. Local policy initiatives such as conservation compliance incentives could help offset local environmental consequences of converting land from CRP to insured production.